The Feasibility and Effectiveness of Integrating Content Knowledge and English Competences for Assessing English Proficiency in CLIL - Ima Isnaini Taufiqur Rohmah (Universitas PGRI Semarang, 2019)
Researching Content and Language Integrated learning (CLIL) is unique since the focus is not only in English as instructional language but we have to consider the content as another side of the coin. Both aspects must be balance. This study aimed exploring the integration of content knowledge and English competence in English proficiency assessment and also the effectiveness of the integration to measure students’ English proficiency. This study used Combined study (Creswell, 2012). The participants of this study were 3 primary schools under the name of International Class Program in East java Indonesia. The data were gathered through semi-structured interview, questionnaire and test, i.e. pre-and-post-test. The qualitative data were analyzed descriptively; and the quantitative data were analyzed by using paired sample t-test formula. The results revealed that integrating content knowledge and English competences in assessing English proficiency is feasible and applicable. Furthermore, it has been statistically proven that it is effective integrating content knowledge and English competences in assessing CLIL by indicated the raise of students’ English proficiency. This study implies that integrating both aspects in CLIL has great influence in students’ English assessment and this should be taken into account by the related parties.